PERMASALAH DAN SOLUSI PEMBELAJARAN DI SEKOLAH DASAR DALAM MENCAPAI TARGET BELAJAR SISWA - Alia Savira; Cindy Ekasari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Keywords: Learning problems, learning solutions, elementary schools, learning motivation, learning strategies, learning media, student learning outcomes. Learning in elementary schools often faces various challenges that can hinder the achievement of student learning targets. These challenges include low learning motivation, differences in individual student abilities, limited use of learning media, and a lack of variety in teaching methods. Furthermore, environmental factors such as parental support and the condition of infrastructure also influence the success of the learning process. If not addressed effectively, these obstacles can lead to suboptimal student learning outcomes and difficulty achieving learning objectives. To address these challenges, appropriate and integrated solutions are needed. Teachers need to implement innovative learning strategies, such as the use of interactive learning media, differentiated learning approaches, and student-centered methods. Furthermore, improving teacher competency through training and professional development is crucial. Support from schools and parents in creating a conducive learning environment is also a contributing factor to success. With the implementation of appropriate solutions, it is hoped that the learning process in elementary schools will be more effective, thus optimally achieving student learning targets.